Copper solution chemistry of cyclic pseudo-octapeptides - Comba, Peter; Dovalil, Nina; Haberhauer, Gebhard; Kowski, Klaus; Mehrkens, Nina; Westphal, Michael (Zeitschrift für anorganische und allgemeine Chemie, 2013)
The CuII solution chemistry of synthetic derivatives of naturally occurring pseudo-octapeptides (patellamides and ascidiacyclamide) is described. The complex stabilities [mono- and dicopper(II) complexes] of five different ligands were determined by isothermal microcalorimetry (ITC), and square wave voltammetry (SQW) was used to elucidate the electrochemical properties. In agreement with published spectroscopic data, there is cooperative binding of two CuII ions and the overall stabilities are, in agreement with known stabilities of the natural ligands and expectations based on the donor sets (two N-based heterocycles and one amide per CuII), only moderate (K ≤ 106). There is a slight dependence of the stabilities on the ligand structure (configuration of the side chains), and that derived from the natural products forms the most stable complexes. Due to the complex equilibria in solution and the instability of the reduced forms, voltammetry shows complex equilibria, which preclude the full assignment of all processes. The positive reduction potentials are in agreement with relatively low complex stabilities. These observations complete earlier studies, concentrating on spectroscopy and structural aspects, and are also discussed in relation to the possible biological function of the cyclic peptides, i.e. metal ion transport, oxygen activation, carboanhydrase, and phosphatase activities.
Gesehen am 04.05.2021